UTILIZATION OF MULTICULTURAL KNOWLEDGE ASSETS IN BUILDING RELIGIOUS MODERATION AT THE ISLAMIC STATE UNIVERSITY OF DATOKARAMA PALU - Saepudin Mashuri; Mohamad Syafri; Rafiiy rahim (Paedagogia: Jurnal Pendidikan, 2023)
This study examines the prominent role of multicultural knowledge assets to be managed and utilized in supporting the success of the religious moderation program in Islamic universities, specifically the State Islamic University of Datokarama Palu. The university was chosen based on its background which focuses on the religious moderation aspect. This study aims to reveal the utilization of multicultural knowledge assets owned by the State Islamic University of Datokarama Palu to build religious moderation. One of the knowledge assets possessed is a multicultural intellectual asset. The method of the study was the qualitative method with a phenomenological approach. The data collection techniques used were interviews and documentation. This study produced several findings, namely; (1) multicultural knowledge does not only come from internal human resources personnel but also the knowledge that is institutional and sourced from external; (2) that multicultural knowledge is relevant to be utilized in the context of building religious moderation based on respect for cultural and religious diversity. However, in several programs, the State Islamic University of Datokarama Palu has not fully utilized the assets of multicultural knowledge. The two seem to be separated from the religious moderation development program. Despite that, both are integral units that need and support each other to build a moderate-academic social life at educational institutions.